Tetrazole as a Carboxylic Acid Isostere and the Synthesis of All Amine‐Based Polyampholytes. Issue 11 (21st April 2022) - Nguyen, Amber; Dallerba, Elena; Lowe, Andrew B.
Abstract: A new family of polyampholytes (PAMs) is described in which both the basic and acidic groups are based on nitrogen functional groups. Reversible addition‐fragmentation chain transfer‐prepared poly(pentafluorophenyl acrylate) is quantitatively modified sequentially with 3‐picolylamine and 5‐aminotetrazole, yielding the new well‐defined statistical PAMs. Successful formation of the PAMs is confirmed via a combination of 19 F and 13 C NMR spectroscopy and FTIR. Aqueous electrophoresis indicates isoelectric points (p I ) between 2.9 and 4.4 depending on copolymer composition. However, the p I is somewhat insensitive to the copolymer composition, a feature attributed to the similarity of the p K a s of the acid tetrazole species and the conjugate acid of the pyridyl repeat units. Abstract : The synthesis of new well‐defined polyampholytes is described based on the carboxylic acid isostere tetrazole. Modification of a reversible addition‐fragmentation chain transfer‐prepared poly(pentafluorophenyl acrylate) homopolymer with 3‐picolylamine and 5‐aminotetrazole, yield the target polyampholytes of varying composition as confirmed by spectroscopic characterization. Aqueous electrophoresis confirms expected polyampholytic behavior.